Tradisi Ketupat Qunutan Malam Ke 15 Bulan Ramadhan di Kampung Pinang (Studi Living Hadis) - Salsabila Alifiya; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The tradition of Ketupat Qunutan on the 15th night of Ramadan in Kampung Pinang, Tangerang City, is a religious practice of the Muslim community that integrates congregational qunut prayers, the making and distribution of ketupat as a symbol of gratitude, almsgiving, purity of heart, and brotherhood. Through a living hadith study approach, this research analyzes how the values of the Sunnah of the Prophet Muhammad SAW, such as communal prayer, food charity, and strengthening Islamic brotherhood, are contextualized within the local culture of the archipelago without a literal textual basis, but rather as a harmonious actualization between Islamic teachings and traditional wisdom. The findings show the dynamics of religious understanding between textual and contextual approaches, in which this tradition strengthens social solidarity, mutual cooperation, and the transmission of the Islamic identity of the archipelago, while also functioning as effective cultural da'wah without contradicting sharia law. This study contributes to the study of Islamic anthropology and living sunnah, affirming cultural acculturation as a form of religious expression that is alive and relevant.